Peroxidase activity of the coronene bisimide supramolecular architecture and its applications in colorimetric sensing of H2O2 and glucose. Issue 32 (15th March 2017) - Yang, Meiding; Zhou, Huipeng; Li, Yongxin; Zhang, Qingfeng; Li, Juanmin; Zhang, Cuiyun; Zhou, Chuibei; Yu, Cong
Abstract : Distinct peroxidase-like catalytic activity of small organic probe self-assembled nanofibers is reported for the first time. Abstract : A new water soluble coronene bisimide derivative (CTDI) was designed and synthesized. CTDI self-assembled in an aqueous solution and formed supramolecular nanofibers through π–π stacking and hydrophobic interactions. The nanofibers exhibit distinct peroxidase-like catalytic activity, and can catalyze the redox reaction of 3, 3, 5, 5-tetramethylbenzidine (TMB) in the presence of hydrogen peroxide. Clear assay solution color changes were observed. The peroxidase-like catalytic property was utilized for the sensitive detection of H2 O2 and glucose. The assay shows excellent sensitivity, and 1 μM of glucose could be easily detected. Glucose detection in dilute human blood samples was also demonstrated, and the results were verified using a commercial glucose meter. Our method is simple, convenient, sensitive and selective, and could facilitate the sensing of glucose in relation to biological and biomedical research applications.